A content analysis of Pulso Ng Bayan segment of TV Patrol - Cabug, Ma. Christine V.; Diva, Elaine Joy H. (1993.)
This study is a content analysis of he Pulso ng bayan segment of T.V. Patrol. A total of twenty episodes were video recorded by the researchers., A self-devised descriptive code sheet was used in anlyzing the data. It has been found out that Pulso ng Bayan mostly presents negative characteristics of the Philippine government and the Filipinos. Findings also revealed that majority of the topics discussed are government politics, followed by government policy education, culture, and science, and peace and order. The average length of the Pulso segment is 147.9 seconds per episode. Results also showed that Noli de Castro consumed the highest average length of time. It was also found out that the Pulso ng Bayan segment mostly gives negative evaluations on how the different issues are being assessed.
Thesis (Undergraduate, Bachelor of Arts in Broadcast Communication) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Pulso ng Bayan -- Content analysis